STRATEGIES FOR THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE: A COMPARATIVE ANALYSIS OF INTERNATIONAL EXPERIENCE - Laura Ashirbekova; Gulzhikhan Smagulova (PEOPLE: International Journal of Social Sciences, 2025)
This article presents a comparative analysis of strategies for integrating artificial intelligence (AI) into public administration. It examines the approaches of various countries to the digital transformation of the public sector through AI technologies, focusing on regulatory frameworks, organizational implementation, and institutional readiness. Particular attention is given to how countries such as the United States, China, Estonia, and the UAE incorporate AI into administrative processes, public service delivery, and decision-making within government institutions. The analysis reveals significant differences in national priorities: from ensuring technological sovereignty and security to developing citizen-oriented services and smart urban infrastructure. Despite these differences, a common objective is evident — to enhance the efficiency, transparency, and adaptability of public administration in a rapidly evolving digital environment. The findings may serve as a valuable resource for developing national AI strategies in the public sector based on international best practices.